MEMBANGUN KARAKTER DAN LOGIKA MATEMATIKA SISWA MELALUI WARISAN BUDAYA NIAS DI DESA BAWONIFAOSO - Laowo, Nasowaauri (Universitas Nias Raya, 2024)
This community service aims to integrate the local wisdom of Nias into character education and mathematical logic in Bawonifoso Village. By utilizing local cultural heritage, such as Nias carving art, which contains geometric patterns, and cultural values such as cooperation, honesty, and respect, this program seeks to shape students' character and enhance their mathematical abilities. The program involves students, teachers, and the local community with a culture-based learning approach. The results show significant improvements in students' character, particularly in the aspects of honesty, responsibility, and cooperation. Additionally, the use of geometric patterns in traditional Nias carving helps students understand mathematical concepts in a more practical and contextual manner. Although there are challenges in implementation, especially in terms of teacher training, this community service contributes positively to culture-based education that can improve the quality of education in the region.